Ab initio calculations of vibrational frequencies in a glassy state of selenium - Rosli, A.N.; Abu Kassim, H.; Shrivastava, K.N. (Penerbit Universiti Kebangsaan Malaysia, 2010)
We used the density functional theory to calculate the vibrational frequencies of clusters of atoms. We obtained the bond distances and angles for which the energy of the Schrodinger equation is minimum. We found the bond distance between two Se atoms to be 232.1 pm when double zeta wave function was used. The frequency of oscillations was calculated to be 325.3 cm(-1) but the intensity was zero because Se(2) molecules were present in a very small number. When polarised double zeta wave function (DZP) was used, the bond length of Se(2) was found to be 223.1 pm and the frequency is 367.4 cm(-1). Similarly for other clusters of selenium, we calculated the frequencies and compared with the experimental data. The experimental Raman spectra give 250 cm(-1) for a selenium glass. By comparing the experimental frequencies with those calculated we found that linear Se(3) was present in the glass. This indicates the possibility of linear growth in the glass.